Teoria crítica, democracia e esfera pública: concepções e usos na américa latina - Leonardo Avritzer; Sérgio Costa (Universidade do Estado do Rio de Janeiro, 2004)
In this article we analyze the construction of the concept of public sphere within critical theory, discussing its recent reformulations and reinterpretations. Our primary aim is to focus on contributions that emphasize the increasing importance of new publics, subaltern counter-publics, diasporic publics, and deliberative publics in contemporary democracies.We seek to outline a broader concept of public sphere in order to offer an adequate instrument for analyzing the simultaneous cycles of democratization and structural adjustment in Latin America.